2018
DOI: 10.1002/stem.2942
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Reprogramming of Cancer Cells and Associated Mesenchymal Stem Cells in Gastric Cancer

Abstract: The interactions of cancer stem cells (CSCs) within the tumor microenvironment (TME), contribute to the overall phenomenon of intratumoral heterogeneity, which also involve CSC interactions with noncancer stromal cells. Comprehensive understanding of the tumorigenesis process requires elucidating the coordinated gene expression between cancer and tumor stromal cells for each tumor. We show that human gastric cancer cells (GSC1) subvert gene expression and cytokine production by mesenchymal stem cells (GSC‐MSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Hitherto, the cellular and molecular mechanisms of MSC transition from BM-MSCs to tumor-derived MSCs have not been clearly elucidated. Accumulating evidences have indicated that cancer cells or their conditioned medium could induce the activation of MSCs to assume a tumor-promoting phenotype ( 65 , 66 ). Moreover, tumor-educated neutrophils were also reported to induce the transformation of MSCs into cancer-associated fibroblasts (CAFs), which in turn remarkably facilitated the growth and metastasis of gastric cancer ( 67 ).…”
Section: Tam-triggered Transition Of Mscs In Gastric Cancermentioning
confidence: 99%
“…Hitherto, the cellular and molecular mechanisms of MSC transition from BM-MSCs to tumor-derived MSCs have not been clearly elucidated. Accumulating evidences have indicated that cancer cells or their conditioned medium could induce the activation of MSCs to assume a tumor-promoting phenotype ( 65 , 66 ). Moreover, tumor-educated neutrophils were also reported to induce the transformation of MSCs into cancer-associated fibroblasts (CAFs), which in turn remarkably facilitated the growth and metastasis of gastric cancer ( 67 ).…”
Section: Tam-triggered Transition Of Mscs In Gastric Cancermentioning
confidence: 99%
“…Despite recent data are therefore questioning the validity of the CSC model, the CSC-MSC interaction is well documented and is crucial for 3D growth and stemness of tumour cells (15), or for the generation of an hybrid MSC-CSC cell populations, occurring via entosis, i.e., a form of cell-to-cell internalization, or via fusion, as demonstrated in different tumours (1620). Indeed, the selection processes of hybrid cells after MSC–tumour cell fusion contribute to CSC development (20, 21).…”
Section: Csc and Mscmentioning
confidence: 99%
“…TA-MSCs with MSC-like properties have become apparent as contributory stromal cells in tumor initiation, progression and metastasis. TA-MSCs have the ability to promote CSC proliferation and to maintain tumor “stemness” in ovarian cancer [49 , 53] , glioma [51] , and gastric cancer [54] . Taken together, these data provide evidence that both MSCs and TA-MSCs play a more potent pro-tumorigenic role in maintaining cancer stemness through increasing CSCs population.…”
Section: Mscs: Contributions To the Cellular Origin Of Cancermentioning
confidence: 99%